2018
DOI: 10.1186/s41240-018-0111-2
|View full text |Cite
|
Sign up to set email alerts
|

Apparent digestibility of dry matter, organic matter, protein and energy of native Peruvian feedstuffs in juvenile rainbow trout (Oncorhynchus mykiss)

Abstract: Trout production is a growing activity in recent years but requires new alternative sources of feed to be sustainable over time. The objective of this research was to determine the apparent digestibility coefficient (ADC) of dry matter (DM), organic matter (OM), crude protein (CP) and digestible energy (DE) of kañiwa (Chenopodium pallidicaule Aellen), kiwicha (Amaranthus caudatus L), quinoa (Chenopodium quinoa Willd), beans (Phaseolus vulgaris L.), sacha inchi, (Plukenetia volubilis L) and jumbo squid (Dosidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
6
1
1
Order By: Relevance
“…Conversely, the inclusion of Y. schidigera in broiler diets showed significantly lower digestibility of DM and ash in the present study. The lower DM digestibility of phytogenic ingredients can be due to the higher composition of fiber in the diet [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the inclusion of Y. schidigera in broiler diets showed significantly lower digestibility of DM and ash in the present study. The lower DM digestibility of phytogenic ingredients can be due to the higher composition of fiber in the diet [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were limited information limited information on how dietary lysine affects ADC of dry matter but a study by Ref. [ 49 ] suggested that a lower value of ADC nutrients might be due to the high fibre content in the diet which decreased the digestibility. Nutritional values of a diet will depend on how efficient its nutrient can be digested, and since there may be interactions amongst the ingredients, the additivity of each ingredient's digestibility should be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…SIM has an obvious bitter taste and is difficult to process directly into food 5 . Currently, SIM is mainly used as a feed ingredient for aquatic animals 6,7 . Protein hydrolysates are defined as a complex mixture of peptides and free amino acids produced by enzymatic hydrolysis, which increases the bioavailability of proteins and reduces the immunoreactivity of native proteins 8 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Currently, SIM is mainly used as a feed ingredient for aquatic animals. 6,7 Protein hydrolysates are defined as a complex mixture of peptides and free amino acids produced by enzymatic hydrolysis, which increases the bioavailability of proteins and reduces the immunoreactivity of native proteins. 8 Studies reported that enzymatically hydrolyzed Sacha inchi protein has antioxidant, antihypertensive, enzyme inhibition (⊍-amylase, ⊍-glucosidase and pancreatic lipase) activities.…”
Section: Introductionmentioning
confidence: 99%